Minoritas Agama di Sekolah Mayoritas: Relasi Antar Umat Beragama pada Sekolah Umum di Provinsi Aceh, Bali dan Sulawesi Utara - Marzuki Marzuki; Mumtazul Fikri (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2022)
This study aims to find patterns of social relations formed in relations between interfaith religious believers and their implications for religious minorities in public high schools in Aceh, Bali, and North Sulawesi. This research is qualitative research with a comparative descriptive method and data collection techniques using interviews, observation, focus group discussion (FGD), and documentation. The location of this research is in Public Senior High School (SMUN) which was selected based on the diversity of students across religions in the provinces of Aceh, Bali, and North Sulawesi. The subjects of this study were principals, teachers, and students at senior high schools in Aceh, Bali, and North Sulawesi Provinces. The results showed that: firstly, the pattern of social relations formed in public schools in three locations, namely Aceh, Bali, and North Sulawesi found that the pattern of associative social relations occurred in Public Senior Schools in Aceh and North Sulawesi Provinces, while the patterns of dissociative social relations occurred in Public Senior Schools in Bali Province. Secondly, the implications of the patterns of social relations formed for religious minorities in public high schools in the three research locations (Aceh, Bali, and North Sulawesi) can be classified into three forms of implications, i.e. spiritual, psychological, and sociological implications.